Histological and Immunohistochemical Features of Trichoblastoma in a Sarda Breed Sheep - Marta Polinas; Giovanni P. Burrai; Veronica Vitiello; Laura Falchi; Maria T. Zedda; Gerolamo Masala; Vincenzo Marras; Giulia Satta; Alberto Alberti; Elisabetta Antuofermo (Animals, 2020)
Skin tumors with adnexal differentiation are commonly reported in dogs and cats, while only anecdotal evidence is available in sheep. Here we illustrate the macroscopic, histologic, and immunohistochemical features of a cutaneous lesion with adnexal differentiation in a 6-year-old female Sarda breed sheep, surgically treated for a horn-like mass located in the left pinna. Additionally, we investigate a possible contribution of Ovine Papillomaviruses (OaPVs). Histologically, the dermis was expanded by an expansive and unencapsulated multilobulated nodule composed of cuboidal to spindle basaloid cells arranged in variably-sized cytokeratins (CK) AE1-AE3, CK 5/6 and CK 34 beta E12, p63—positive winding cords with a characteristic palisade arrangement of neoplastic cells in the periphery of the tumor. Based on these results, the cutaneous neoplasm was diagnosed as a trabecular trichoblastoma with spindle cells and rare structures resembling papillary mesenchymal bodies. Additionally, multiple enlarged sebaceous lobules clustered around dilated ducts suggestive of sebaceous gland hyperplasia were detected near the trichoblastoma. No PV DNA was found in the examined tissues, suggesting that ovine PVs are not involved in the pathogenesis of the present skin tumors with adnexal differentiation. Further investigations and efforts are required to elucidate the prevalence of skin tumors with adnexal differentiation in this species.